2008
DOI: 10.4049/jimmunol.180.12.7907
|View full text |Cite|
|
Sign up to set email alerts
|

Central Memory CD8+ T Cells Appear to Have a Shorter Lifespan and Reduced Abundance as a Function of HIV Disease Progression

Abstract: Progressive HIV disease has been associated with loss of memory T cell responses to Ag. To better characterize and quantify long-lived memory T cells in vivo, we have refined an in vivo labeling technique to study the kinetics of phenotypically distinct, low-frequency CD8+ T cell subpopulations in humans. HIV-negative subjects and antiretroviral-untreated HIV-infected subjects in varying stages of HIV disease were studied. After labeling the DNA of dividing cells with deuterated water (2H2O), 2H-label incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
79
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 64 publications
(69 reference statements)
2
79
4
Order By: Relevance
“…ϩ T CM cells in HIV-1 patients, a recent study suggested that the CD8 ϩ T CM half-life seems reduced from a 1/2 of ϳ100 days to a 1/2 of ϳ50 days (8). Even if we used a 1/2 of ϳ50 days for latently HIV-1 infected CD4…”
mentioning
confidence: 99%
“…ϩ T CM cells in HIV-1 patients, a recent study suggested that the CD8 ϩ T CM half-life seems reduced from a 1/2 of ϳ100 days to a 1/2 of ϳ50 days (8). Even if we used a 1/2 of ϳ50 days for latently HIV-1 infected CD4…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that the differentiation status of T cells is associated with the rate of HIV disease progression (4,20,34,40,47). Burgers et al (4) showed that higher frequencies of early CD8 memory cells during early HIV infection were associated with subsequently lower viral set points.…”
mentioning
confidence: 99%
“…Further, individuals who are able to better control HIV infection have a preserved CM pool, (40,47), while individuals with a reduced CM CD4 pool had increased plasma HIV load (20).…”
mentioning
confidence: 99%
“…Additionally, we measured these processes in multiple anatomic compartments. Previous studies employed mathematical modeling to hypothesize in vivo cell kinetics outside of the circulation while measuring deuterium label gain and loss in circulating cells (18,19,21,22,24,27,30,(50)(51)(52)(53)(54). In contrast, we obtained quantitative measurements of deuterium gain and loss in T cell subsets from lymphoid and target organs, and we found the same subset (i.e., Treg) to behave differently in the spleen compared with the liver.…”
Section: Discussionmentioning
confidence: 38%